Glaciological study in Terra Nova Bay, Antarctica inferred from remote sensing analysis - Massimo Frezzotti (Annals of Glaciology, 1993)
Analysis of satellite images (Landsat 1 MSS, 4 TM and SPOT 1 XS), of U.S. Navy aerial photographs (TMA) and of U.S.G.S. maps has made it possible to assess a number of parameters relating to the surface dynamics (between 1956 and 1990) of eight ice tongues and of two ice shelves in the Terra Nova Bay area. The study shows that between 1960–63 and 1972–73 there was a decided decrease in the areas of some of the tongues and shelves: −53 km2 for the Aviator Glacier Tongue and −124 km2 for the Nansen Ice Sheet. On the other hand, the areas generally increased in the period 1972–73 to 1988. An exception to this situation is the small Hells Gate ice shelf whose area diminished by 1.15 km2 between 1956–57 and 1988. The calculated surface velocity of the ice tongues shows that they increase from the grounding line to their outer limit. Values of longitudinal strain rate generally increase from the grounding line to just after the start of the ice tongue, after which they diminsh proceeding towards its outer limit. Integration of the areal values with radio-echo sounding data has enabled the ice discharges of the southern flow of the David Glacier (12km3a−1) and of the Aviator Glacier Tongue (0.62 km3 a−1) to be calculated. Furthermore, on the basis of the data available, basal melting values of between 25 cm a−1 and 100 cm a−1 are deduced for these two ice tongues, and bottom freezing values of 20 cm a−1 for the Drygalski Ice Tongue. Different spectral responses of the glacial areas have made it possible to discriminate ablation areas from those of accumulation and to differentiate various typologies of ice (glacier ice, melt lake ice, and sea ice formed at the ice shelf-ocean interface).